2012
DOI: 10.1097/igc.0b013e318253a994
|View full text |Cite
|
Sign up to set email alerts
|

Variant Lineages of Human Papillomavirus Type 18 in Northeast China Populations Characterized by Sequence Analysis of E6, E7, and L1 Regions

Abstract: Based on the E6 gene, the prevalent HPV 18 in Northeast China was AA and E variants. Besides some common variations reported before, some new variations in the E6, E7, and L1 genes were found. Data about the novel variations found in the L1 gene of HPV 18 variants may be helpful to design the diagnostic reagents and vaccine for naturally infected HPV 18 in Northeast China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Our LCR/E6 classification fits with other HPV18 sequences reported in the literature (10,12,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) and is consistent with lineage definitions based on the gold standard approach of HPV18 whole-genome sequencing (13). Although based on LCR and E6 only, our analysis included many novel variants, particularly among previously underrepresented A5 and B (sub)lineages, which would warrant sequencing the whole genomes in order to strengthen the full picture of HPV18 genetic evolution.…”
Section: Discussionsupporting
confidence: 48%
“…Our LCR/E6 classification fits with other HPV18 sequences reported in the literature (10,12,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) and is consistent with lineage definitions based on the gold standard approach of HPV18 whole-genome sequencing (13). Although based on LCR and E6 only, our analysis included many novel variants, particularly among previously underrepresented A5 and B (sub)lineages, which would warrant sequencing the whole genomes in order to strengthen the full picture of HPV18 genetic evolution.…”
Section: Discussionsupporting
confidence: 48%
“…Over 200 HPV types have been identified based on L1 sequences. HPV18 variants were originally grouped into European (E), Asian-Amerindian (AA) or African (AFR) lineages according to E6-E7, L1, and/or LCR sequences [10][11][12][13][14]. This classification has been superseded by a whole viral genome sequencing approach that has defined three major lineages (A, B, and C) and additional sublineages (A1 to A5 and B1 to B3) [15] that can be translated from the historical nomenclature (A1 and A2 are AA, A3 to A5 are E and B/C are AFR) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Speci c variations of HPV 18 may present high oncogenic potential and in uence the variation of distribution of cervical cancer in different regions (20). However, a study by Villa et al (2000) indicated that infection by non-European variants presents a greater chance of persistence of infection and association with pre-invasive lesions (20,22). Thus, more research is needed to understand which factors may be associated with virus lineages in the persistence and progression of cervical lesions.…”
Section: Discussionmentioning
confidence: 99%